The Implementation of the Problem-Based Learning (PBL) Model to Improve Student Activeness in Elementary School - , (Edumaspul: Jurnal Pendidikan, 2026)
This research is motivated by the low student activity in the subject of science at UPT SDN 004 Salo, Salo District, Kampar Regency. One solution to overcome this problem is to research the Problem Based Learning (PBL) learning model. The purpose of this study is to describe the application of the Problem Based Learning (PBL) learning model to increase student activity. The research method is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection, and the research time is carried out in June 2025. The subjects of this study were 25 fifth grade students, with 11 boys and 14 girls. The collection techniques are documentation, observation and tests. The results of the study can be concluded that the activeness of students using the Problem Based Learning (PBL) learning model for class V of SDN 004 Salo in cycle I is classified as Sufficient with an average of 60 and cycle I meeting II is classified as Good with an average of 76. Furthermore, classical learning completeness is 44%. In cycle II it is good with an average of 84 and in cycle II meeting II it is classified as very good with an average of 100. Furthermore, classical learning completeness is 88%. Thus, it can be concluded that using the Problem Based Learning (PBL) learning model can increase the activeness of class V students of SDN 004 Salo.